Display element and photosensitive resin composition used therefor

By using a composition of an alkali-soluble resin and a fluorine-based resin, combined with an ethylene unsaturated compound and a photoinitiator, the problems of low liquid removability and light transmittance in the prior art are solved, and an organic electroluminescent element is realized Excellent performance and reliability.

CN119213898APending Publication Date: 2024-12-27DONGJIN SEMICHEM CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380041236.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-03
Filing Date
2023-04-25
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The conventional photosensitive resin composition for organic electroluminescent elements exhibits deteriorated liquid repellency and light transmittance when forming partition patterns, resulting in a decrease in reliability and a decrease in photoreactivity.

Method used

By using a composition of an alkali-soluble resin and a fluorine-based resin, a partition wall material with excellent liquid removability and ink leveling is formed by controlling the surface energy of the exposed part and the non-exposed part, combining an ethylene unsaturated compound and a photoinitiator.

Benefits of technology

Excellent color performance, liquid removal, coating properties, defoaming characteristics, ink leveling and optical density are achieved, extending the life of the display element and improving reliability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119213898A_ABST
    Figure CN119213898A_ABST
Patent Text Reader

Abstract

The present invention relates to a display element and a photosensitive resin composition applicable to the display element, the photosensitive resin composition having excellent sensitivity, coating properties, defoaming properties, liquid repellency in an exposed portion, leveling properties in a non-exposed portion, and the like, and being capable of forming an optical member exhibiting improved optical properties. The method is suitable for forming partition walls of various display elements such as OLEDs.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a display element and a photosensitive resin composition used therefor, wherein the display element comprises a partition wall exhibiting improved optical properties, wherein the optical properties include excellent liquid repellency and excellent leveling of ink for OLED, QD-OLED, WOLED, QNED and other displays within the pixel. Background Art

[0002] Recently, organic electroluminescent elements are widely used as display elements in various electronic devices using thin displays such as smartphones, tablet computers, and televisions.

[0003] Generally, such an organic electroluminescent element has the following structure: a light-transmitting first electrode formed on the light extraction side and a non-light-transmitting second electrode formed on the other side are formed on the substrate, and an organic light-emitting layer that defines each pixel such as red, green and blue is formed between the first electrode and the second electrode. In addition, a partition wall structure is formed between each pixel to divide these pixels and prevent color mixing. In order to prevent color mixing and ensure element reliability by using the partition wall structure between pixels filled with display ink, excellent liquid repellency is required at the top of the partition wall, and excellent ink leveling is required inside the pixel.

[0004] Such partition wall structure is usually formed using a photosensitive resin composition containing black pigment to prevent the visibility and contrast of the display element from being reduced due to external light reflection. When the pixel segmentation layer pattern (partition wall pattern) is formed using the above-mentioned photosensitive resin composition containing black pigment, the partition wall structure exhibits high light shielding properties, thereby suppressing external light reflection, so that the display element such as the organic electroluminescent element can exhibit excellent visibility, etc.

[0005] Typically, it is known that the pixel division layer pattern can be formed using a photosensitive resin composition containing an alkali-soluble resin such as a polyimide resin having a photocurable functional group, a black pigment, a polyfunctional compound having a photocurable functional group, and a photoinitiator.

[0006] However, when such a conventional photosensitive resin composition is used to form a partition wall pattern, the partition wall pattern formed eventually exhibits deteriorated liquid repellency, thus having the disadvantage of reduced reliability. In addition, due to the effect of the black pigment, the overall light transmittance of the photosensitive resin composition decreases, and the desired level of light transmittance cannot be exhibited, thereby reducing the photoreactivity and sensitivity.

[0007] Therefore, there is a need to continuously develop a photosensitive resin composition that can improve the overall characteristics of the partition wall pattern in a display element such as an organic electroluminescent element. Summary of the invention

[0008] Technical issues to be solved

[0009] In view of this, the present invention is intended to provide a display element.

[0010] The present invention also aims to provide a photosensitive resin composition which can form a cured film having low surface energy by mixing an alkali-soluble resin and a fluorine-based resin, and the cured film can be used for the display element.

[0011] Technical solutions for solving the above technical problems

[0012] The present invention provides a display element, comprising partition walls and a color filter layer defined by the partition walls.

[0013] The partition wall comprises:

[0014] Alkali soluble resin derivatives; and

[0015] Fluorine resin derivatives,

[0016] The surface energy of the exposed part is less than 35 dyne / cm.

[0017] The surface energy of the non-exposed portion is 35 dyne / cm or more.

[0018] In addition, the present invention provides a photosensitive resin composition for forming a partition wall of the display element, comprising:

[0019] a) alkali soluble resin;

[0020] b) Fluorine resin;

[0021] c) ethylenically unsaturated compounds; and

[0022] d) Photoinitiator.

[0023] Effects of the Invention

[0024] According to the display element of the present invention, the exposed portion and the non-exposed portion exhibit specific surface energy values, so no spots are generated, excellent color expression can be achieved, and the problem of reduced life of the display element caused by outgassing can be solved.

[0025] In addition, the photosensitive resin composition according to the present invention, for example, contains the specific fluorine-based resin of Chemical Formula 1 together with the alkali-soluble resin, and therefore, when applied to partition walls of a display element, can exhibit excellent liquid repellency and provide excellent sensitivity, coating properties, defoaming properties, ink leveling, reliability and optical density. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1Cured film patterns and EL and Al vapor deposition molding shapes used to evaluate the reliability of Examples and Comparative Examples are schematically shown. DETAILED DESCRIPTION

[0027] In the following, the present invention will be described in more detail. The terms or words used in this specification and claims should not be interpreted as limited to the conventional or dictionary meanings, and should be interpreted as the meanings and concepts that conform to the technical ideas of the present invention, on the principle that the inventor can appropriately define the concepts of the terms to describe the present invention in the best way.

[0028] In addition, the word “comprising” used in the description of the present invention means to concretize a certain characteristic, field, integer, step, operation, element and / or component, and does not exclude the existence or addition of other characteristics, fields, integers, steps, operations, elements and / or components.

[0029] In the specification, "(meth)acrylate" means both "acrylate" and "methacrylate".

[0030] In the specification, the weight average molecular weight is the polystyrene conversion weight average molecular weight measured by GPC, and the weight average molecular weight is measured by the standard analysis method of the gel permeation chromatography (GPC) system used as the e2695 Alliance Separation Module of Waters. Three types of Acquity APC XT (2.5μm, 4.6mmx 150mm).

[0031] Hereinafter, the embodiments will be described in detail so that those skilled in the art can easily implement the present invention. The embodiments can be implemented in various ways and are not limited to the specific embodiments described herein.

[0032] Display components

[0033] According to a specific example of the present invention, a display element may be provided, comprising:

[0034] Partition walls; and

[0035] The color filter layer defined by the partition wall,

[0036] The partition wall comprises:

[0037] Alkali soluble resin derivatives; and

[0038] Fluorine resin derivatives,

[0039] The surface energy of the exposed part is less than 35 dyne / cm.

[0040] The surface energy of the non-exposed portion is 35 dyne / cm or more.

[0041] The display element of the above-mentioned specific example may include a partition wall, wherein the partition wall includes both an alkali-soluble resin and a fluorine-based resin.

[0042] The surface energy of the exposed portion of the partition wall may be less than 35 dyne / cm, and the surface energy of the non-exposed portion may be greater than 35 dyne / cm. When the surface energy of the exposed portion is less than 35 dyne / cm, no spots or the like will be generated due to the pigments and other color materials constituting the color filter layer remaining on the partition wall. In terms of the generation of spots, it is preferably less than 30 dyne / cm. In addition, since the surface energy of the non-exposed portion is greater than 35 dyne / cm, the wettability with the ink used to form the color filter layer can be improved.

[0043] On the other hand, when the surface energy of the exposed and non-exposed parts of the partition wall exceeds the numerical range, problems such as color mixing caused by ink remaining on the partition wall, or reduced wettability with the ink may cause a reduction in the pixel area of ​​the color filter layer, which may lead to poor reliability of the display element.

[0044] The surface energy of the exposed part and the non-exposed part can be measured by the following mathematical formula 1. Specifically, the surface energy (γ) of the exposed part and the non-exposed part can be measured by the following mathematical formula 1 using ultrapure water and diiodomethane. s ).

[0045] [Mathematical formula 1]

[0046] (1+cosθ) / 2=[(γ s d ) 1 / 2 (γ l d ) 1 / 2 ] / γ l +[(γ s p ) 1 / 2 (γ l p ) 1 / 2 ] / γ l ]

[0047] In the above mathematical formula 1,

[0048] θ is the contact angle between a drop of ultrapure water and diiodomethane dropped on the sample surface and the surface.

[0049] γ sd represents the dispersive force, γ s p represents polar interaction,

[0050] Surface energy (γ s ) was determined as γ s d With γ s p The sum of

[0051] γ l , γ l d , and γ l p Use the following values,

[0052] Ultrapure water: γ l =72.8dyne / cm,γ l d =21.8dyne / cmγ l p =51.0dyne / cm,

[0053] Diiodomethane: γ l =50.8dyne / cm,γ l d =49.5dyne / cmγ l p =1.3dyne / cm.

[0054] In the display element of the above-mentioned specific example, the partition wall may include a derivative derived from an alkali-soluble resin. The alkali-soluble resin may include at least one alkali-soluble resin selected from acrylic resin, polyimide resin, siloxane resin and phenolic resin. Generally, cardo resin is used as an alkali-soluble resin for forming a color filter, but when used for forming a partition wall, due to reflow, etc., there may be problems such as difficulty in forming the desired pattern partition wall and achieving resolution.

[0055] Therefore, preferably, the partition wall of the display element may include a derivative derived from at least one alkali-soluble resin of acrylic resin, polyimide resin, siloxane resin and phenolic resin. For example, as the phenolic resin, polyhydroxystyrene resin, phenolic resin, etc. can be used. The partition wall of the display element includes a derivative derived from at least one alkali-soluble resin of acrylic resin, polyimide resin, siloxane resin and phenolic resin, and since reflow does not occur, the desired pattern partition wall can be easily formed and excellent resolution can be achieved.

[0056] In the display element of the above specific example, the partition wall may include a derivative derived from a fluorine-based resin. The derivative is a substance derived from a fluorine-based resin in the partition wall forming composition, and the fluorine-based resin may preferably include a fluorine-based resin having a weight average molecular weight of 30,000 to 300,000.

[0057] When a fluorine-based resin having a molecular weight within the above range is included, a partition wall having a surface energy of a specific value can be formed by controlling process conditions such as exposure and heat treatment.

[0058] However, when a fluorine-based resin having a molecular weight smaller than the above range is included, the liquid repellency of the partition wall may be reduced, and when a fluorine-based resin having a molecular weight larger than the above range is included, there may be a problem of reduced coating properties.

[0059] In the display element of the above-mentioned specific example, the fluorine atomic ratio in the cross section of the exposed part of the partition wall may be 0.001 to 1 mass%. When the fluorine atomic ratio is less than 0.001 mass%, since the surface energy of the top of the partition wall is greater than 35 dyne / cm, problems such as color mixing caused by the ink remaining on the partition wall may also occur. When the fluorine atomic ratio is greater than 1 mass%, there is a possibility of problems with coating and defoaming characteristics. Since the surface energy of the non-exposed part is less than 35 dyne / cm, the leveling property of the ink in the pixel decreases, and poor reliability of the display element may also occur.

[0060] The fluorine atom content in fluorine-based resins is determined by 19 F NMR and 1 The fluorine atom content in the exposed portion of the partition wall was calculated by H NMR, and was a theoretical value calculated from the fluorine atom content in the fluorine-based resin in the total solid raw material.

[0061] In the display element of the above specific example, the surface energy of the non-exposed part of the partition wall may be greater than 40 dyne / cm, and the surface energy of the exposed part may be less than 25 dyne / cm. Preferably, the surface energy difference between the non-exposed part and the exposed part may be greater than 15 dyne / cm.

[0062] When the surface energy of the non-exposed part and the exposed part is greater than or less than or equal to a specific value, especially when the surface energy difference between the non-exposed part and the exposed part is greater than 15 dyne / cm, the partition wall exhibits excellent liquid repellency and further improves the wettability with the ink used to form the color filter, thereby further improving the luminescent properties of the display element.

[0063] In the display element of the above specific example, the optical density (OD) of the partition wall may be 0.1 to 3.0, and the optical density may be defined by the following Mathematical Formula 2.

[0064] [Mathematical formula 2]

[0065] Optical density (OD) = 2-logT550

[0066] In the above Mathematical Formula 2, T550 represents the light transmittance (%) with respect to light of 550 nm measured at a thickness of 1 μm.

[0067] When the optical density of the partition wall falls within the numerical range, excellent light resistance can be exhibited. To this end, the partition wall may contain a color material such as a black pigment.

[0068] In one specific example, the display element may include partition walls formed by the following preparation method.

[0069] Specifically, a photosensitive resin composition comprising an alkali-soluble resin and a fluorine-based resin is coated on a target substrate, the portion of the residual partition wall pattern is exposed through a photomask to photocure the composition of the exposed portion, and the composition of the remaining unexposed portion is treated with an alkaline developer (for example, a 0.041 wt % potassium hydroxide aqueous solution, etc.), so that a partition wall pattern can be formed by development and removal methods.

[0070] More specifically, the partition wall can be prepared by the following method.

[0071] For example, the photosensitive resin composition may be coated on a substrate by spin coating, slit coating, slit coating followed by spin coating, inkjet coating, etc., pre-dried in a vacuum chamber, and then pre-baked using a hot plate or oven to form a cured film.

[0072] The substrate includes, for example, a silicon substrate, a silicon nitride substrate, a substrate coated with a metal such as aluminum, molybdenum, chromium, etc., a glass substrate, a quartz substrate, an ITO substrate, etc.

[0073] The pre-bake heat treatment conditions may be an optimal heating temperature and a heating time selected from the range of 0.5 minutes to 10 minutes at a temperature of 75° C. to 150° C.

[0074] In addition, the thickness of the cured film may be, for example, 0.5 μm to 15 μm.

[0075] Then, after the exposed portion is developed using an alkaline developer, the exposed portion of the cured film formed of the photosensitive resin is cured, and a pattern in accordance with the shape of the mask is formed.

[0076] As a developing method, an immersion method, a shaking immersion method, etc. can be used. At this time, the developing time can be 20 seconds to 180 seconds, but is not limited thereto.

[0077] After the development, the photosensitive resin cured film is washed with running water for, for example, 20 to 120 seconds, and then dried with compressed air or compressed nitrogen or by spin drying, thereby obtaining a film with a pattern formed after removing moisture from the substrate.

[0078] Next, the pattern is post-baked to complete thermal curing, specifically by heating with a hot plate or an oven, to obtain a cured film having excellent heat resistance, flattening performance, low water absorption, etc. and having a good pattern. Such a cured film is included in a display element as a partition wall, thereby improving the performance of the display element.

[0079] As the post-bake heat treatment condition, a method of treating on a hot plate for 5 to 60 minutes or in an oven for 20 to 180 minutes at a heating temperature selected generally in the range of 75°C to 300°C may be adopted.

[0080] A specific example of a display element may be an organic light emitting element (OLED). However, the display element is not limited to OLED, and any display element including a partition wall and a color filter layer may be used.

[0081] Photosensitive resin composition

[0082] According to a specific example of the present invention, a photosensitive resin composition for forming a partition wall of the display element may be provided, comprising:

[0083] a) alkali soluble resin;

[0084] b) Fluorine resin;

[0085] c) ethylenically unsaturated compounds; and

[0086] d) Photoinitiator.

[0087] At this time, the fluorine-based resin may include repeating units represented by the following Chemical Formulas 1 and 1-1.

[0088] [Chemical formula 1]

[0089]

[0090] [Chemical formula 1-1]

[0091]

[0092] In the above chemical formulas 1 and 1-1,

[0093] a and b represent the mole ratio between the repeating units, a+b=100, a (fluorine monomer) is 10 to 60, and the mole ratio between the repeating units is based on 2D-NMR (H-NMR, F-NMR) analysis,

[0094] x and y are each an integer from 1 to 8,

[0095] R1 and R2 are each independently hydrogen or methyl,

[0096] R3 is a fluoroalkyl group having 1 to 20 carbon atoms which may have an ethereal oxygen atom, and a part of the fluorine in at least one of the fluoroalkyl groups may be substituted with hydrogen.

[0097] R4 is a branched group having 0 to 50 carbon atoms and having any one or more structures selected from the group consisting of a carbamate group, a urea group, an amino group, a hydroxyl group, an acryloyl group, an ether group, and an ester group.

[0098] The photosensitive resin composition of the above specific example is mixed with an alkali-soluble resin such as a fluorine-based resin containing repeating units of specific structures such as the above Chemical Formulas 1 and 1-1, so that a cured film having a lower surface energy than a conventional cured film can be formed.

[0099] Therefore, the cured film formed by the photosensitive resin composition of the above-mentioned specific example can show excellent liquid repellency and ink leveling, and can show improved coating properties, transmittance, photoreactivity and sensitivity. In addition, when the photosensitive resin composition of a specific example contains a black pigment or a black pigment mixture, the cured film also shows all the above-mentioned characteristics, and can show excellent light resistance due to excellent optical density.

[0100] Therefore, the cured film formed from the photosensitive resin composition according to the above-mentioned specific example can be suitably used as a liquid-repellent partition wall material for various display elements such as an organic electroluminescent element.

[0101] Hereinafter, a specific example of the photosensitive resin composition will be described in detail according to each component.

[0102] First, a specific example of the composition includes a predetermined alkali-soluble resin. The alkali-soluble resin may include at least one selected from the group consisting of a) acrylic resin, polyimide resin, siloxane resin and phenolic resin.

[0103] In addition, for the above-mentioned alkali-soluble resin, the degree of polymerization can be adjusted to a polystyrene-equivalent weight average molecular weight of 1,000 to 30,000. In this case, the light transmittance, sensitivity and photoreactivity of a specific example of the composition can be further improved, and the cured film formed from the specific example of the composition can exhibit excellent light resistance, optical density, adhesion and residual film properties. In addition, as long as the alkali-soluble resin is adjusted to have the above-mentioned weight average molecular weight, a copolymer prepared by a method known in the art can be selected, and its type is not too limited.

[0104] Specifically, the acrylic resin may be one or more acrylic copolymers selected from the group consisting of Synthesis Examples A-1 to A-4 described later in the examples. The polystyrene-equivalent weight average molecular weight of the acrylic resin may be 1,000 to 30,000.

[0105] The phenolic resin is a conventional alkali-soluble resin containing a phenol structure, and a typical phenolic resin can be used. The phenolic resin can be, for example, one or more selected from the group consisting of Synthesis Examples A-5 to A-8 described later in the Examples, and the polystyrene-converted weight average molecular weight of such phenolic resin can be 1,000 to 30,000.

[0106] The siloxane resin can be synthesized by the method of Synthesis Example A-13 described later in the Examples. The polystyrene-equivalent weight average molecular weight of the siloxane resin can be 1,000 to 30,000.

[0107] The polyimide resin may contain at least one polyimide precursor or a polyimide structure as a repeating unit of the resin, and may be synthesized by the method of Synthesis Example A-14 described later in the Examples. For such a polyimide resin, the polystyrene-converted weight average molecular weight may be 1,000 to 30,000.

[0108] On the other hand, a specific example of the photosensitive resin composition may include b) a fluorine-based resin including a repeating unit represented by the following Chemical Formulas 1 and 1-1.

[0109] [Chemical formula 1]

[0110]

[0111] [Chemical formula 1-1]

[0112]

[0113] In the above chemical formulas 1 and 1-1,

[0114] a and b represent the mole ratio between the repeating units, a+b=100, and a (fluorine monomer) is 10 to 60. The mole ratio between the repeating units is based on 2D-NMR (H-NMR, F-NMR) analysis,

[0115] x and y are each an integer from 1 to 8,

[0116] R1 and R2 are each independently hydrogen or methyl,

[0117] R3 is a fluoroalkyl group having 1 to 20 carbon atoms and may have an ethereal oxygen atom, and a portion of the fluorine in at least one of the groups may be substituted with hydrogen, for example, a fluoroalkyl group such as -(CF2)oCF3, -(CF2)pCF2H, or -CF2(OCF2CF2)qCF3 (wherein o and p are each independently an integer from 1 to 7, and q is an integer from 1 to 3),

[0118] R4 is a branched group having 0 to 50 carbon atoms and having any one or more structures selected from the group consisting of a carbamate group, a urea group, an amino group, a hydroxyl group, an acryloyl group, an ether group, and an ester group.

[0119] For the fluorine-based resin comprising the repeating units of the above chemical formulas 1 and 1-1, by including a repeating unit a (fluorine monomer) having an R3 substituent in an acrylic structure and a repeating unit b (acrylic monomer) having a branched group such as R4 in an acrylic structure, the ink leveling property of the photosensitive resin composition can be improved, and the surface energy can be reduced to improve the liquid repellency.

[0120] In particular, for the fluorine-based resin of the above chemical formula 1, when a urea or ammonia structure is introduced into R4 of the acrylic monomer using an amino group, and a carbamate structure is introduced using a long-chain alcohol, flexibility can be increased, thereby increasing reactivity with an alkali-soluble resin or an ethylenically unsaturated compound. Therefore, the liquid repellency of the cured film of the photosensitive resin composition according to the above specific example and the ink leveling property of the non-exposed portion can be improved.

[0121] In addition, in the fluorine-based resin, the molar ratio of repeating unit a (fluorine monomer) to repeating unit b (acrylic monomer) may be 10 to 60%: 90 to 40% based on 100% of the total molar number of the fluorine-based resin. At this time, if the molar ratio of a in the molar ratio of repeating unit a (fluorine monomer): repeating unit b (acrylic monomer) is less than 10%, the surface energy of the cured film increases, and there is a problem of reduced liquid repellency. If the molar ratio of a is greater than 60%, there is a problem of reduced ink leveling in the non-exposed area of ​​the composition.

[0122] In addition, the repeating unit b (acrylic monomer) represents a long chain length of 0 to 50 carbon atoms. When urea, ammonia or urea structure is introduced, flexibility is increased, thereby improving the reactivity with alkali-soluble resins or ethylenically unsaturated compounds, thereby increasing the liquid repellency of the cured film and the ink leveling property of the non-exposed portion.

[0123] At this time, R4 in the above chemical formula 1-1 may be a structure of the following chemical formula 1-2:

[0124] [Chemical formula 1-2]

[0125]

[0126] In the above chemical formula 1-2, m is an integer from 0 to 5,

[0127] Z1 and Z3 each independently represent an organic group having 1 to 20 carbon atoms,

[0128] Z2 is an organic group containing any one or more structures of a carbamate group, a urea group, a hydroxyl group, an ether group, and an ester group,

[0129] R1 is hydrogen or methyl.

[0130] As an example, R4 of the above Chemical Formula 1-1 may be a substituent selected from the group represented by the following Chemical Formulas 2 to 6.

[0131] [Chemical formula 2]

[0132]

[0133] In the above chemical formula 2, R1 is hydrogen or methyl, X2 represents an organic group having 1 to 20 carbon atoms,

[0134] [Chemical formula 3]

[0135]

[0136] In the above chemical formula 3, R1 is hydrogen or methyl, X3 represents an organic group having 1 to 20 carbon atoms, and m is an integer from 1 to 5.

[0137] [Chemical formula 4]

[0138]

[0139] In the above chemical formula 4, R1 is hydrogen or methyl, X4 represents an organic group having 1 to 20 carbon atoms, and m is an integer from 1 to 5.

[0140] [Chemical formula 5]

[0141]

[0142] In the above chemical formula 5, R1 is hydrogen or methyl, X6 represents an organic group having 1 to 20 carbon atoms, and m is an integer from 1 to 5.

[0143] [Chemical formula 6]

[0144]

[0145] In the above chemical formula 6, R1 is hydrogen or methyl, X 10 represents an organic group having 1 to 20 carbon atoms, and l is an integer of 1 to 13.

[0146] In the fluorine-based resins of the above chemical formulae 2 to 6, X2, X3, X4, X6 and X 10 Each of the organic groups having 1 to 20 carbon atoms may be an alkylene group having 1 to 20 carbon atoms or an arylene group having 4 to 20 carbon atoms. More specifically, the above-mentioned X2, X3, X4, X6 and X 10 Each of the organic groups having 1 to 20 carbon atoms may be an alkylene group such as methylene, ethylene, methylethylene, propylene, methylpropylene, tetramethylene, hexamethylene, octamethylene, decamethylene, isobutylene, or the like, or an arylene group such as phenylene.

[0147] Regarding the above b) fluorine-based resin, the weight average molecular weight may be 30,000 to 300,000.

[0148] If the molecular weight of the fluorine-based resin is 30,000 or less, the liquid repellency of the cured film and the ink leveling property of the non-exposed portion may be deteriorated. If the molecular weight of the fluorine-based resin is 300,000 or more, the coating property of the photosensitive resin composition and the defoaming property due to bubble generation may be deteriorated.

[0149] On the other hand, according to the present invention, the fluorine-based resin not only has the above-mentioned structure but also has a weight average molecular weight that satisfies the above-mentioned range, thereby reducing the surface energy of the cured film formed by curing with the alkali-soluble resin, thereby improving not only the liquid repellency and ink leveling properties but also the light resistance. In addition, even if the photosensitive resin composition contains a black pigment or a black pigment mixture, it can also show greatly improved liquid repellency, ink leveling properties, optical density and light resistance.

[0150] As a more specific example of such a fluorine-based resin, for example, one or more selected from the group consisting of the above Chemical Formula 4 and Chemical Formula 6. When one or more fluorine-based resins selected from the group consisting of the above Chemical Formula 4 and Chemical Formula 6 are used, more excellent liquid repellency, light resistance, ink leveling, sensitivity, coating properties, defoaming characteristics, and reliability can be achieved.

[0151] Moreover, b) the fluorine-based resin may be used in an amount of 0.01 to 10 parts by weight based on the total solid content representing the total content of a) the alkali-soluble resin, c) the ethylenically unsaturated compound, and d) the photoinitiator.

[0152] If the content of the fluorine-based resin is less than 0.01 parts by weight, it may be difficult to form the partition wall with an exposure surface energy of less than 35 dyne / cm, preferably less than 30 dyne / cm, and there is a problem of reduced liquid repellency of the partition wall. If the excess amount of the fluorine-based resin reaches more than 10 parts by weight, there is a problem of reduced coating properties, defoaming characteristics and ink leveling properties.

[0153] On the other hand, a specific example of the photosensitive resin composition includes c) an ethylenically unsaturated compound. The ethylenically unsaturated compound includes a multifunctional compound having a plurality of photocurable unsaturated functional groups. The ethylenically unsaturated compound undergoes a photocuring reaction with the above-mentioned alkali-soluble resin in the exposed part of the photosensitive resin composition under the mediation of a photoinitiator, thereby forming a cross-linked structure, which can define a partition wall and a pixel segmentation layer pattern that will not be removed by a developer.

[0154] The ethylenically unsaturated compound may have various photocurable unsaturated functional groups, but more preferably may have the same type of unsaturated functional groups as the above-mentioned alkali-soluble resin, for example, a (meth)acrylate functional group.

[0155] More specifically, the ethylenically unsaturated compound may include a multifunctional acrylic monomer or a urethane acrylate monomer.

[0156] The multifunctional acrylic monomer may include one or more selected from the group consisting of 1,4-butanediol diacrylate, 1,3-butanediol diacrylate, ethylene glycol diacrylate, trimethylol propane diacrylate, trimethylol propane triacrylate, pentaerythritol triacrylate, pentaerythritol tetraacrylate, triethylene glycol diacrylate, polyethylene glycol diacrylate, dipentaerythritol hexaacrylate, dipentaerythritol triacrylate, dipentaerythritol diacrylate, sorbitol triacrylate, bisphenol A diacrylate derivatives, dipentaerythritol polyacrylate and methacrylates thereof.

[0157] The urethane acrylate oligomer may include at least one selected from the group consisting of aliphatic urethane (meth)acrylate oligomers having 2 to 20 unsaturated functional groups, aromatic urethane (meth)acrylate oligomers, epoxy (meth)acrylate oligomers, polyester (meth)acrylate oligomers, silicone (meth)acrylate oligomers, melamine (meth)acrylate oligomers and dendritic (meth)acrylate oligomers.

[0158] More specific examples of the ethylenically unsaturated compound include at least one selected from the group consisting of dipentaerythritol hexaacrylate, dipentaerythritol pentaacrylate, ditrimethylolpropane tetraacrylate, trimethylolpropane triacrylate, tricyclodecane dimethanol diacrylate, and 1,6-hexanediol diacrylate.

[0159] However, the type of the ethylenically unsaturated compound is not particularly limited, and any polyfunctional compound previously known to be usable in a photosensitive resin composition or commercially available polyfunctional (meth)acrylate compounds may be used without particular limitation.

[0160] On the other hand, one specific example of the composition further comprises d) a photoinitiator. The photoinitiator can initiate and promote the photocuring and crosslinking reaction between the alkali-soluble resin and the multifunctional compound in the exposed area.

[0161] The photoinitiator may be any photoinitiator previously known to be applicable to the photosensitive resin composition without particular limitation, and as an example, one or more selected from the group consisting of carbazole initiators, oxime ester initiators, aminoalkylphenone initiators, and acylphosphine oxide initiators may be cited. More specific examples of the photoinitiator may be one or more selected from the group consisting of 2-octanediol-1[(4-phenylthio)phenyl]-2-benzoyl-oxime, 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl]ethanone-1-O-acetyloxime, (E)-2-(acetoxyimino)-1-(9,9-diethyl-9H-fluoren-2-yl)butanone, and phenyl(4-methoxyphenyl)arsenic iodide hexafluoride, and various other photoinitiators may be used.

[0162] The above-mentioned photosensitive resin composition of a specific example may contain 10 to 200 parts by weight of c) ethylenically unsaturated compounds and 1 to 20 parts by weight of d) photoinitiators relative to 100 parts by weight of a) alkali-soluble resin. When the content of each component exceeds the above range, it may cause the visibility of the display element to decrease, or the light resistance, optical density, residual film characteristics and adhesion of the cured film to decrease, or the sensitivity, photoreactivity or light transmittance of the composition to decrease.

[0163] On the other hand, the photosensitive resin composition of one specific example may further include at least one selected from the group consisting of e) a black pigment or a pigment mixture containing a pigment that exhibits black color in a mixed state, and f) a silane coupling agent.

[0164] The photosensitive resin composition contains the above-mentioned e) black pigment or pigment mixture to suppress light reflection of the photosensitive resin composition and the cured film, thereby improving the visibility or contrast of the display element. In addition, due to the inclusion of such black pigment, the light resistance and optical density of the cured film formed from the composition can be further improved.

[0165] As the black pigment, either an organic black pigment or an inorganic black pigment can be used. For example, the black pigment can be selected from the group consisting of aniline black, perylene black, titanium black, cyanine black, lignin black, lactam black, carbon black, RGB black, RBY black, and RBV black without particular limitation.

[0166] In addition, the pigment may also include a pigment mixture containing multiple pigments of different colors mixed to form a black pigment mixture as a whole. According to a more specific example, the pigment mixture may be a pigment mixture containing two or more selected from red pigment, blue pigment, yellow pigment, green pigment and purple pigment to form a black pigment mixture as a whole.

[0167] At this time, as specific examples of pigments of different colors used to obtain the pigment mixture, one or more selected from the group consisting of CI pigment yellow, CI pigment red, CI pigment violet, CI pigment blue and CI pigment green can be cited. In addition, various additional pigments can also be used. In other words, according to a ratio that is obvious to ordinary technicians, these multiple pigments of different colors are mixed to obtain a pigment mixture that is black as a whole. A specific example of the composition can include the pigment mixture.

[0168] On the other hand, in addition to the above-mentioned black pigment or pigment mixture, it can of course further contain the above-mentioned additional pigments of different colors.

[0169] The pigment including the black pigment or the pigment mixture may be a particle-type pigment having a particle size of 100 to 200 nm. By using such a fine particle size pigment, the light resistance or visibility of the display element can be further improved.

[0170] In addition, the pigment can be mixed with other components in the form of a pigment dispersion dispersed in an organic solvent (for example, one or more organic solvents selected from the group consisting of propylene glycol methyl ether, γ-butyrolactone, propylene glycol methyl ether acetate and ethyl lactate) so that it can be uniformly dispersed or dissolved after being appropriately mixed with other components.

[0171] The above-mentioned f) silane coupling agent may include (3-glycidyloxypropyl)trimethoxysilane, (3-glycidyloxypropyl)triethoxysilane, (3-glycidyloxypropyl)methyldimethoxysilane, (3-glycidyloxypropyl)methyldiethoxysilane, (3-glycidyloxypropyl)dimethylethoxysilane, 3,4-epoxybutyltrimethoxysilane, 3,4-epoxybutyltriethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, )ethyltriethoxysilane, aminopropyltrimethoxysilane, aminopropyltriethoxysilane, 3-triethoxysilyl-n-(1,3-dimethyl-butylene)propylamine, n-2(aminoethyl)3-aminopropyltrimethoxysilane, n-2(aminoethyl)3-aminopropyltriethoxysilane, n-2(aminoethyl)3-aminopropylmethyldimethoxysilane, n-phenyl-3-aminopropyltrimethoxysilane and (3-isocyanatepropyl)triethoxysilane are selected from the group consisting of one or more thereof, thereby improving the adhesion characteristics.

[0172] On the other hand, a specific example of the photosensitive resin composition may further include g) an organic solvent for dissolving or dispersing the above-mentioned components. The content of this organic solvent may be such that the solid content of the total composition is 10 to 50% by weight, so that the above-mentioned components are uniformly dissolved or dispersed, and processes such as solvent removal are easily performed. In other words, according to a specific example, the photosensitive resin composition further includes g) an organic solvent, and the solid content may be 10 to 50% by weight.

[0173] The type of such organic solvent is not particularly limited, and any solvent previously known to be useful in photosensitive resin compositions may be used, for example, one or more organic solvents selected from the group consisting of aromatic hydrocarbon solvents, aliphatic hydrocarbon solvents, ester solvents, ether solvents, alcohol solvents, amide solvents and ketone solvents.

[0174] More specifically, the organic solvent may include one or more selected from the group consisting of propylene glycol methyl ether acetate, propylene glycol ether acetate, propylene glycol propyl ether acetate, methyl methoxypropionate, ethyl methoxypropionate, propylene glycol methyl ether propionate, propylene glycol ethyl ether propionate, propylene glycol propyl ether propionate, propylene glycol ether, propylene glycol ethyl ether, propylene glycol propyl ether, propylene glycol butyl ether, diethylene glycol diethyl ether, diethylene glycol methyl ethyl ether, dipropylene glycol dimethyl ether, dibutyl glycol dimethyl ether, dibutyl glycol diethyl ether, diethylene glycol butyl methyl ether, diethylene glycol butyl ether, triethylene glycol dimethyl ether, triethylene glycol butyl methyl ether, diethylene glycol tert-butyl ether, tetraethylene glycol dimethyl ether, dipropylene glycol ethyl ether, diethylene glycol ethyl hexyl ether, diethylene glycol methyl hexyl ether, dipropylene glycol butyl methyl ether, propylene glycol ethyl hexyl ether and dipropylene glycol methyl hexyl ether.

[0175] Hereinafter, examples are given to help understand the present invention. However, the following examples are only used to illustrate the present invention and are not intended to limit the present invention to the following examples.

[0176] <Preparation of alkali-soluble resin>

[0177] Acrylic resin

[0178] [Synthesis Example A-1]

[0179] A mixed solution of 500 parts by weight of tetrahydrofuran, 30 parts by weight of methacrylic acid and 70 parts by weight of glycidyl methacrylate was added to a flask equipped with a cooling tube and a stirrer, and then 10 parts by weight of 2,2'-azobis(2,4-dimethylvaleronitrile) was added. After nitrogen substitution in the flask, the reaction solution was slowly stirred and heated to 55°C for 24 hours to prepare a polymer solution containing an acrylic copolymer.

[0180] The polymer solution including the acrylic copolymer was purified and then dried to prepare an acrylic copolymer having a weight average molecular weight of 7,000.

[0181] At this time, the weight average molecular weight is measured by a standard analysis method using gel permeation chromatography (GPC) used as e2695 Alliance Separation Module of Water Co. The weight average molecular weight is a polystyrene-equivalent average molecular weight measured using GPC.

[0182] [Synthesis Example A-2]

[0183] An acrylic copolymer was prepared by the same method as in Synthesis Example A-1 except that 20 parts by weight of methacrylic acid, 60 parts by weight of 3,4-epoxycyclohexyl methacrylate and 20 parts by weight of styrene were used instead of 30 parts by weight of methacrylic acid and 70 parts by weight of glycidyl methacrylate in Synthesis Example A-1.

[0184] The weight average molecular weight of the acrylic copolymer synthesized according to Synthesis Example A-2 was 5,000.

[0185] At this time, the weight average molecular weight is measured by a standard analysis method using gel permeation chromatography (GPC) used as e2695 Alliance Separation Module of Water Co. The weight average molecular weight is a polystyrene-equivalent average molecular weight measured using GPC.

[0186] [Synthesis Example A-3]

[0187] A mixed solution of 500 parts by weight of tetrahydrofuran, 20 parts by weight of acrylic acid, 50 parts by weight of 1,2-epoxy-4-vinylcyclohexane and 30 parts by weight of styrene was added to a flask equipped with a cooling tube and a stirrer, and then 20 parts by weight of 2,2'-azobis(2,4-dimethylvaleronitrile) was added. After nitrogen substitution in the flask, the reaction solution was slowly stirred and heated to 60°C for 48 hours to prepare a polymer solution containing an acrylic copolymer.

[0188] The polymer solution including the acrylic copolymer was purified and then dried to prepare an acrylic copolymer having a weight average molecular weight of 8,000.

[0189] At this time, the weight average molecular weight is measured by a standard analysis method using gel permeation chromatography (GPC) used as e2695 Alliance Separation Module of Water Co. The weight average molecular weight is a polystyrene-equivalent average molecular weight measured using GPC.

[0190] [Synthesis Example A-4]

[0191] A mixed solution of 400 parts by weight of tetrahydrofuran, 20 parts by weight of methacrylic acid, 50 parts by weight of 3,4-epoxycyclohexyl methacrylate, 15 parts by weight of dicyclofentanylmethacrylate and 15 parts by weight of styrene was added to a flask equipped with a cooling tube and a stirrer, and then 20 parts by weight of 2,2'-azobis(2,4-dimethylvaleronitrile) was added. After nitrogen substitution in the flask, the reaction solution was slowly stirred and heated to 60°C for 24 hours to prepare a polymer solution containing an acrylic copolymer.

[0192] The polymer solution including the acrylic copolymer was purified and then dried to prepare an acrylic copolymer having a weight average molecular weight of 5,000.

[0193] At this time, the weight average molecular weight is measured by a standard analysis method using gel permeation chromatography (GPC) used as e2695 Alliance Separation Module of Water Co. The weight average molecular weight is a polystyrene-equivalent average molecular weight measured using GPC.

[0194] Phenolic resin

[0195] [Synthesis Example A-5]

[0196] 70 parts by weight of m-cresol and 30 parts by weight of p-cresol were added to a flask equipped with a cooling tube and a stirrer, and then 0.2 parts by weight of oxalic acid was added. After nitrogen was replaced in the flask, the reaction solution was slowly stirred and heated to 80°C. When the temperature reached 80°C, 18 parts by weight of formaldehyde was added dropwise for 1 hour, and then the temperature was raised to 110°C for 6 hours to prepare a polymer.

[0197] The polymer solution including the polymer was purified and then dried to prepare a phenolic polymer having a weight average molecular weight of 6,000.

[0198] At this time, the weight average molecular weight is measured by a standard analysis method using gel permeation chromatography (GPC) used as e2695 Alliance Separation Module of Water Co. The weight average molecular weight is a polystyrene-equivalent average molecular weight measured using GPC.

[0199] [Synthesis Example A-6]

[0200] 100 parts by weight of o-cresol and 0.3 parts by weight of oxalic acid were added to a flask equipped with a cooling tube and a stirrer, and after the flask was replaced with nitrogen, the reaction solution was slowly stirred and heated to 80° C. When the temperature reached 80° C., 20 parts by weight of formaldehyde was added dropwise for 1 hour, and the temperature was raised to 110° C. for 6 hours to prepare a polymer.

[0201] 300 parts by weight of epichlorohydrin, 3 parts by weight of tetramethylammonium chloride and 100 parts by weight of dimethyl sulfoxide were added to the polymer and slowly stirred, and then 15 parts by weight of sodium hydroxide were added in batches for 1 hour. Then, the reaction was stirred for 6 hours, and the unreacted matter was removed under reduced pressure after the reaction was completed.

[0202] After adding 100 parts by weight of 4-methylpentanone and 5 parts by weight of sodium hydroxide to the reactant, the mixture was reacted at 100° C. for 6 hours, and then washed with water and purified to synthesize a polymer.

[0203] A mixed solution of 100 parts by weight of propylene glycol monomethyl ether acetate, 100 parts by weight of the polymer, and 35 parts by weight of acrylic acid was added to a flask equipped with a cooling tube and a stirrer, and then 1 part by weight of tetramethylammonium chloride and 0.001 part by weight of 2,6-di-tert-butyl-4-methylphenol were added. After nitrogen substitution in the flask, the reaction solution was slowly stirred and heated to 110° C. for 5 hours to prepare a polymer.

[0204] The polymer solution including the polymer was purified and then dried to prepare a polymer having a weight average molecular weight of 6,000.

[0205] At this time, the weight average molecular weight is measured by a standard analysis method using gel permeation chromatography (GPC) used as e2695 Alliance Separation Module of Water Co. The weight average molecular weight is a polystyrene-equivalent average molecular weight measured using GPC.

[0206] [Synthesis Example A-7]

[0207] A mixed solution of 100 parts by weight of propylene glycol monomethyl ether acetate and 100 parts by weight of the final synthetic product of the synthesis example A-6 was added to a flask with a cooling tube and an agitator, and then 3 parts by weight of benzyltriethylammonium bromide were added. After the flask was replaced with nitrogen, it was slowly stirred, and after the reaction solution was heated to 130°C, 25 parts by weight of 4,4'-oxydiphthalic anhydride was added, and then reacted for 6 hours. After confirming the exhaustion of the anhydride group by FT-IR (Fourier Transform Infrared Spectroscopy), 13 parts by weight of terephthalic anhydride was added, and then reacted for 4 hours, and the exhaustion of the anhydride group was confirmed by FT-IR.

[0208] After the temperature of the reactor was lowered to room temperature, 200 parts by weight of propylene glycol monomethyl ether acetate was added for dilution, followed by purification and drying to prepare a polymer having a weight average molecular weight of 6,700.

[0209] At this time, the weight average molecular weight is measured by a standard analysis method using gel permeation chromatography (GPC) used as e2695 Alliance Separation Module of Water Co. The weight average molecular weight is a polystyrene-equivalent average molecular weight measured using GPC.

[0210] [Synthesis Example A-8]

[0211] A phenol polymer was prepared by the same method as in Synthesis Example A-7, except that phenol was used instead of o-cresol.

[0212] The weight average molecular weight of the polymer synthesized according to Synthesis Example A-8 was 6,500, and the weight average molecular weight was measured by a standard analysis method using gel permeation chromatography (GPC) used as e2695 Alliance Separation Module of Water Co. The weight average molecular weight is a polystyrene-equivalent average molecular weight measured using GPC.

[0213] Cardo Resin

[0214] [Synthesis Example A-9]

[0215] Synthesis of Bisphenol Fluorene Epoxy Acrylate (a1)

[0216] 100 parts by weight of 4,4'-(9-fluorenyl)diphenol and 300 parts by weight of epichlorohydrin were added to a flask equipped with a cooling tube and a stirrer, and then 3 parts by weight of tetramethylammonium chloride and 100 parts by weight of dimethyl sulfoxide were added. The reaction solution was slowly stirred, and after heating to 100°C, 15 parts by weight of sodium hydroxide were added in batches for 1 hour. Then, the reaction was stirred for 6 hours, and after the reaction was completed, the unreacted product was removed under reduced pressure.

[0217] After adding 4-methylpentanone and 100 parts by weight of sodium hydroxide to the reactant, the mixture was reacted at 100° C. for 6 hours, and then washed with water and purified to synthesize a polymer (a1).

[0218] Synthesis of Bisphenol Fluorene Epoxy Acrylate (a2)

[0219] A mixed solution of 100 parts by weight of propylene glycol monomethyl ether acetate, 100 parts by weight of the polymer (a1), and 35 parts by weight of acrylic acid was added to a flask with a cooling tube and a stirrer, and then 1 part by weight of tetramethylammonium chloride and 0.001 part by weight of 2,6-di-tert-butyl-4-methylphenol were added. After nitrogen substitution in the flask, the reaction solution was slowly stirred and heated to 110°C for 5 hours to prepare a polymer. After the reaction was completed, the reaction solution was washed with water and purified to synthesize a polymer (a2).

[0220] Polymerization of bisphenol fluorene epoxy acrylate and acid dianhydride (a3)

[0221] In a flask equipped with a cooling tube and a stirrer, 100 parts by weight of propylene glycol monomethyl ether acetate and 100 parts by weight of the polymer (a2) were added and mixed thoroughly, and then 3 parts by weight of benzyltriethylammonium bromide was added. After the temperature was raised to 130° C., 25 parts by weight of 4,4'-oxydiphthalic anhydride was added, and then the reaction was carried out for 6 hours. After confirming that the anhydride group was exhausted by FT-IR (Fourier Transform Infrared Spectroscopy), 13 parts by weight of terephthalic anhydride was added, and then the reaction was carried out for 4 hours.

[0222] After the temperature of the reactor was lowered to room temperature, 200 parts by weight of propylene glycol monomethyl ether acetate was added for dilution, followed by purification and drying to prepare a polymer having a weight average molecular weight of 5,000.

[0223] At this time, the weight average molecular weight is measured by a standard analysis method using gel permeation chromatography (GPC) used as e2695 Alliance Separation Module of Water Co. The weight average molecular weight is a polystyrene-equivalent average molecular weight measured using GPC.

[0224] [Synthesis Example A-10]

[0225] In Synthesis Example A-9, a polymer was prepared by the same method as in Synthesis Example A-9, except that 4,4'-(hexafluoroisopropylene)diphthalic anhydride was used in place of 4,4'-oxydiphthalic anhydride in the polymerization of the polymer a3.

[0226] The weight average molecular weight of the polymer synthesized according to Synthesis Example A-10 was 7,000.

[0227] At this time, the weight average molecular weight is measured by a standard analysis method using gel permeation chromatography (GPC) used as e2695 Alliance Separation Module of Water Co. The weight average molecular weight is a polystyrene-equivalent average molecular weight measured using GPC.

[0228] [Synthesis Example A-11]

[0229] In Synthesis Example A-9, a polymer was prepared by the same method as in Synthesis Example A-9 except that 4,4'-(4,4'-isopropylidenediphenoxy)bis(phthalic anhydride) was used in place of 4,4'-oxydiphthalic anhydride in the polymerization of the polymer a3.

[0230] The weight average molecular weight of the polymer synthesized according to Synthesis Example A-11 was 8,500.

[0231] At this time, the weight average molecular weight is measured by a standard analysis method using gel permeation chromatography (GPC) used as e2695 Alliance Separation Module of Water Co. The weight average molecular weight is a polystyrene-equivalent average molecular weight measured using GPC.

[0232] [Synthesis Example A-12]

[0233] In the above Synthesis Example A-9, a polymer was prepared by the same method as in the above Synthesis Example A-9, except that 3,3',4,4'-biphenyltetracarboxylic anhydride was used instead of 4,4'-oxydiphthalic anhydride in the polymerization of the polymer a3.

[0234] The weight average molecular weight of the polymer synthesized according to Synthesis Example A-12 was 5,500.

[0235] At this time, the weight average molecular weight is measured by a standard analysis method using gel permeation chromatography (GPC) used as e2695 Alliance Separation Module of Water Co. The weight average molecular weight is a polystyrene-equivalent average molecular weight measured using GPC.

[0236] Silicone resin

[0237] [Synthesis Example A-13]

[0238] In a flask with a cooling tube and a stirrer, 40 parts by weight of 3-glycidyl ether propyl trimethoxysilane and 60 parts by weight of tetraethoxysilane were placed as reactive silanes, and the atmosphere was replaced with nitrogen and then slowly stirred. Furthermore, 50 parts by weight of ultrapure water and 4 parts by weight of oxalic acid were added to the reaction solution relative to the solid matter, and then slowly stirred. After 1 hour, the reaction solution was heated to 60°C and kept warm for 12 hours for polymerization, and then cooled to room temperature to terminate the reaction. The water and alcohol components generated in the reaction were removed by vacuum drying at a temperature below 30°C to synthesize a siloxane resin containing epoxy groups and hydroxyl groups with a weight average molecular weight of 3,000.

[0239] At this time, the weight average molecular weight is measured by a standard analysis method using gel permeation chromatography (GPC) used as e2695 Alliance Separation Module of Water Co. The weight average molecular weight is a polystyrene-equivalent average molecular weight measured using GPC.

[0240] Polyimide Precursor

[0241] [Synthesis Example A-14]

[0242] 400 parts by weight of γ-butyrolactone and 100 parts by weight of 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane were placed in a flask with a cooling tube and a stirrer, and slowly stirred at 60°C to dissolve them. 95 parts by weight of 3,3',4,4'-biphenyltetracarboxylic dianhydride was added to the reaction solution, and after reacting at 70°C, 30 parts by weight of phthalic anhydride was added to react for 4 hours. The reaction was terminated to synthesize a polyimide precursor with a weight average molecular weight of 3,000.

[0243] At this time, the weight average molecular weight is measured by a standard analysis method using gel permeation chromatography (GPC) used as e2695 Alliance Separation Module of Water Co. The weight average molecular weight is a polystyrene-equivalent average molecular weight measured using GPC.

[0244] <Preparation of Fluorine-Based Resin of Chemical Formula 1>

[0245] [Synthesis Example B-1]

[0246] A mixed solution of 200 parts by weight of tetrahydrofuran, 10 parts by weight of an unsaturated compound containing a fluorine unit represented by the following chemical formula 1A, and 90 parts by weight of (hydroxyethyl) methacrylate was added to a flask with a cooling tube and a stirrer, and then 10 parts by weight of 2,2'-azobis(2,4-dimethylvaleronitrile) was added. After nitrogen substitution in the flask, the reaction solution was slowly stirred and heated to 50°C for 24 hours to prepare an acrylic copolymer. The polymer solution containing the polymer was purified and dried to prepare a final acrylic copolymer.

[0247] 400 parts by weight of tetrahydrofuran, 100 parts by weight of the acrylic copolymer and 50 parts by weight of 2-isocyanatoethyl acrylate were added and mixed thoroughly, and then 0.05 parts by weight of dibutyltin dilaurate was added, and then the temperature was raised to 40° C. and kept for 12 hours to react.

[0248] The weight average molecular weight of the final polymer was 30,000. At this time, the weight average molecular weight was measured by a standard analysis method using gel permeation chromatography (GPC) used as the e2695 Alliance Separation Module of Water Company. The weight average molecular weight is the average molecular weight in terms of polystyrene measured using GPC. The column combination used was a pore size of Three types of Acquity APC XT (2.5μm, 4.6mm x150mm).

[0249] [Chemical Formula 1A]

[0250]

[0251] [Synthesis Example B-2]

[0252] In a flask with a cooling tube and a stirrer, 200 parts by weight of tetrahydrofuran, 20 parts by weight of an unsaturated compound containing a fluorine unit represented by the following chemical formula 2A, and 80 parts by weight of an unsaturated compound containing a hydroxyl group represented by the following chemical formula 2B were added, and then 11 parts by weight of 2,2'-azobis(2,4-dimethylvaleronitrile) were added. After nitrogen substitution in the flask, the reaction solution was slowly stirred and heated to 55°C for 20 hours to prepare an acrylic copolymer.

[0253] After adding 400 parts by weight of tetrahydrofuran, 100 parts by weight of the acrylic copolymer and 45 parts by weight of 2-isocyanatoethyl acrylate and mixing them thoroughly, 0.05 parts by weight of dibutyltin dilaurate was added, and then the temperature was raised to 40° C. and kept for 12 hours for reaction. After the reaction was completed, the polymer solution was purified and dried, and the weight average molecular weight of the final polymer was 40,000.

[0254] At this time, the weight average molecular weight is measured by the standard analysis method of gel permeation chromatography (GPC) used in the e2695 Alliance Separation Module of Water Company. The weight average molecular weight is the average molecular weight in terms of polystyrene measured by GPC. The column combination used is a pore size of Three types of Acquity APC XT (2.5μm, 4.6mm x 150mm).

[0255] [Chemical Formula 2A]

[0256]

[0257] [Chemical formula 2B]

[0258]

[0259] [Synthesis Example B-3]

[0260] A mixed solution of 400 parts by weight of propylene monomethyl ether acetate, 20 parts by weight of an unsaturated compound containing a fluorine unit represented by the following chemical formula 3A, and 80 parts by weight of glycidyl methacrylate was added to a flask equipped with a cooling tube and a stirrer, and then 7 parts by weight of 2,2'-azobis(2,4-dimethylvaleronitrile) was added. After nitrogen substitution in the flask, the reaction solution was slowly stirred and heated to 60°C for 24 hours to prepare an acrylic copolymer.

[0261] 35 parts by weight of acrylic acid and 0.05 parts by weight of tetramethylammonium chloride were added to the copolymer to dissolve them, and then reacted at 110° C. for 6 hours. The polymer solution containing the polymer was purified and then dried to prepare a final acrylic copolymer.

[0262] The weight average molecular weight of the final polymer was 50,000. At this time, the weight average molecular weight was measured using the standard analysis method of gel permeation chromatography (GPC) used as the e2695 Alliance Separation Module of Water Company. The weight average molecular weight is the average molecular weight in terms of polystyrene measured using GPC. The column combination used a pore size of Three types of Acquity APC XT (2.5μm, 4.6mm x150mm).

[0263] [Chemical formula 3A]

[0264]

[0265] [Synthesis Example B-4]

[0266] A flask with a cooling tube and a stirrer is added with 600 parts by weight of tetrahydrofuran, 40 parts by weight of an unsaturated compound containing a fluorine unit represented by the following chemical formula 4A, and 60 parts by weight of an unsaturated compound represented by the following chemical formula 4B having two unsaturated groups, and then 15 parts by weight of 2,2'-azobis(2,4-dimethylvaleronitrile) are added. After nitrogen replacement of the flask, the reaction solution is slowly stirred and heated to 55°C for 20 hours to prepare an acrylic copolymer. The polymer solution containing the polymer is purified and dried to prepare a final acrylic copolymer.

[0267] The weight average molecular weight of the final polymer was 100,000. At this time, the weight average molecular weight was measured by a standard analysis method using gel permeation chromatography (GPC) used as the e2695 Alliance Separation Module of Water Company. The weight average molecular weight is the average molecular weight in terms of polystyrene measured using GPC. The column combination used a pore size of Three types of Acquity APC XT (2.5μm, 4.6mm x150mm).

[0268] [Chemical Formula 4A]

[0269]

[0270] [Chemical Formula 4B]

[0271]

[0272] In the above Chemical Formula 4B, n is 4.

[0273] [Synthesis Example B-5]

[0274] A mixed solution of 200 parts by weight of tetrahydrofuran, 60 parts by weight of an unsaturated compound containing a fluorine unit represented by the following chemical formula 5A, and 40 parts by weight of (hydroxyethyl) methacrylate was added to a flask equipped with a cooling tube and a stirrer, and then 5 parts by weight of 2,2'-azobis(2,4-dimethylvaleronitrile) was added. After nitrogen substitution in the flask, the reaction solution was slowly stirred and heated to 55° C. for 24 hours to prepare an acrylic copolymer.

[0275] 400 parts by weight of tetrahydrofuran, 100 parts by weight of the acrylic copolymer and 30 parts by weight of 2-isocyanate acrylate were added and mixed thoroughly, and then 0.05 parts by weight of dibutyltin dilaurate was added, and then the temperature was raised to 35° C. and kept for 12 hours to react.

[0276] The polymer solution containing the polymer was purified and then dried to prepare a final polymer, and the weight average molecular weight of the polymer was 150,000.

[0277] At this time, the weight average molecular weight is measured by the standard analysis method of gel permeation chromatography (GPC) used in the e2695 Alliance Separation Module of Water Company. The weight average molecular weight is the average molecular weight in terms of polystyrene measured by GPC. The column combination used is a pore size of Three types of Acquity APC XT (2.5μm, 4.6mm x 150mm).

[0278] [Chemical Formula 5A]

[0279]

[0280] [Synthesis Example B-6]

[0281] A mixed solution of 200 parts by weight of tetrahydrofuran, 60 parts by weight of an unsaturated compound containing a fluorine unit represented by the following chemical formula 6A, and 40 parts by weight of an unsaturated compound containing a hydroxyl group represented by the above chemical formula 2B was added to a flask with a cooling tube and a stirrer, and then 4.5 parts by weight of 2,2'-azobis(2,4-dimethylvaleronitrile) was added. After nitrogen replacement of the flask, the reaction solution was slowly stirred and heated to 60°C for 48 hours to prepare an acrylic copolymer. The polymer solution containing the polymer was purified and dried to prepare a final acrylic copolymer.

[0282] 400 parts by weight of tetrahydrofuran, 100 parts by weight of the acrylic copolymer and 25 parts by weight of 2-isocyanate acrylate were added and mixed thoroughly, and then 0.05 parts by weight of dibutyltin dilaurate was added, and then the temperature was raised to 40° C. and kept for 12 hours to react.

[0283] The weight average molecular weight of the final polymer was 200,000. At this time, the weight average molecular weight was measured by a standard analysis method using gel permeation chromatography (GPC) used as the e2695 Alliance Separation Module of Water Company. The weight average molecular weight is the average molecular weight in terms of polystyrene measured using GPC. The column combination used a pore size of Three types of Acquity APC XT (2.5μm, 4.6mm x150mm).

[0284] [Chemical Formula 6A]

[0285]

[0286] [Synthesis Example B-7]

[0287] A mixed solution of 400 parts by weight of propylene monomethyl ether acetate, 10 parts by weight of an unsaturated compound containing a fluorine unit represented by the following chemical formula 7A, and 90 parts by weight of glycidyl methacrylate was added to a flask equipped with a cooling tube and a stirrer, and then 12 parts by weight of 2,2'-azobis(2,4-dimethylvaleronitrile) was added. After nitrogen substitution in the flask, the reaction solution was slowly stirred and heated to 55° C. for 24 hours to prepare an acrylic copolymer.

[0288] 35 parts by weight of acrylic acid and 0.05 parts by weight of tetramethylammonium chloride were added to the copolymer to dissolve them, and then reacted at 110° C. for 6 hours. The polymer solution containing the polymer was purified and then dried to prepare a final acrylic copolymer.

[0289] The weight average molecular weight of the final polymer was 30,000. At this time, the weight average molecular weight was measured by a standard analysis method using gel permeation chromatography (GPC) used as the e2695 Alliance Separation Module of Water Company. The weight average molecular weight is the average molecular weight in terms of polystyrene measured using GPC. The column combination used was a pore size of Three types of Acquity APC XT (2.5μm, 4.6mm x150mm).

[0290] [Chemical Formula 7A]

[0291]

[0292] [Synthesis Example B-8]

[0293] A mixed solution of 600 parts by weight of solid tetrahydrofuran, 10 parts by weight of an unsaturated compound containing a fluorine unit represented by the following chemical formula 8A, and 90 parts by weight of an unsaturated compound represented by the above chemical formula 4B having two unsaturated groups was added to a flask with a cooling tube and a stirrer, and then 18 parts by weight of 2,2'-azobis(2,4-dimethylvaleronitrile) was added. The flask was replaced with nitrogen and slowly stirred, and the reaction solution was slowly stirred and heated to 50°C for 16 hours to prepare an acrylic copolymer.

[0294] The weight average molecular weight of the final polymer was 40,000. At this time, the weight average molecular weight was measured by a standard analysis method using gel permeation chromatography (GPC) used as the e2695 Alliance Separation Module of Water Company. The weight average molecular weight is the average molecular weight in terms of polystyrene measured using GPC. The column combination used a pore size of Three types of Acquity APC XT (2.5μm, 4.6mm x150mm).

[0295] [Chemical Formula 8A]

[0296]

[0297] [Synthesis Example B-9]

[0298] A mixed solution of 200 parts by weight of tetrahydrofuran, 30 parts by weight of an unsaturated compound containing a fluorine unit represented by the following chemical formula 9A, and 70 parts by weight of (hydroxyethyl) methacrylate was added to a flask equipped with a cooling tube and a stirrer, and then 7.5 parts by weight of 2,2'-azobis(2,4-dimethylvaleronitrile) was added. After nitrogen substitution in the flask, the reaction solution was slowly stirred and heated to 60°C for 24 hours to prepare an acrylic copolymer.

[0299] After adding 400 parts by weight of tetrahydrofuran, 100 parts by weight of the acrylic copolymer and 42 parts by weight of 2-isocyanatoethyl acrylate and mixing them thoroughly, 0.05 parts by weight of dibutyltin dilaurate was added, and then the temperature was raised to 40° C. and kept for 6 hours to react. After the reaction was completed, the polymer solution containing the polymer was purified and dried to prepare the final acrylic copolymer.

[0300] The weight average molecular weight of the final polymer was 50,000. At this time, the weight average molecular weight was measured using the standard analysis method of gel permeation chromatography (GPC) used as the e2695 Alliance Separation Module of Water Company. The weight average molecular weight is the average molecular weight in terms of polystyrene measured using GPC. The column combination used a pore size of Three types of Acquity APC XT (2.5μm, 4.6mm x150mm).

[0301] [Chemical Formula 9A]

[0302]

[0303] [Reference Synthesis Example 1]

[0304] A mixed solution of 400 parts by weight of propylene monomethyl ether acetate, 10 parts by weight of an unsaturated compound containing a fluorine unit represented by the above chemical formula 1A, and 90 parts by weight of glycidyl methacrylate was added to a flask with a cooling tube and a stirrer, and then 13 parts by weight of 2,2'-azobis(2,4-dimethylvaleronitrile) was added. After nitrogen substitution in the flask, the reaction solution was slowly stirred and heated to 55° C. for 24 hours to prepare an acrylic copolymer.

[0305] 35 parts by weight of acrylic acid and 0.05 parts by weight of tetramethylammonium chloride were added to the copolymer to dissolve them, and then reacted at 110° C. for 6 hours. The polymer solution containing the polymer was purified and then dried to prepare a final acrylic copolymer.

[0306] The weight average molecular weight of the final polymer was 14,000. At this time, the weight average molecular weight was measured by a standard analysis method using gel permeation chromatography (GPC) used as the e2695 Alliance Separation Module of Water Company. The weight average molecular weight is the average molecular weight in terms of polystyrene measured using GPC. The column combination used a pore size of Three types of Acquity APC XT (2.5μm, 4.6mm x150mm).

[0307] [Reference Synthesis Example 2]

[0308] A mixed solution of 600 parts by weight of tetrahydrofuran, 20 parts by weight of an unsaturated compound containing a fluorine unit represented by the above chemical formula 2A, and 80 parts by weight of an unsaturated compound represented by the above chemical formula 4B having two unsaturated groups was added to a flask with a cooling tube and a stirrer, and then 10 parts by weight of 2,2'-azobis(2,4-dimethylvaleronitrile) was added. After nitrogen substitution in the flask, the reaction solution was slowly stirred and heated to 55°C for 16 hours to prepare an acrylic copolymer.

[0309] The weight average molecular weight of the final polymer was 310,000. At this time, the weight average molecular weight was measured by a standard analysis method using gel permeation chromatography (GPC) used as the e2695 Alliance Separation Module of Water Company. The weight average molecular weight is the average molecular weight in terms of polystyrene measured using GPC. The column combination used a pore size of Three types of Acquity APC XT (2.5μm, 4.6mm x150mm).

[0310] [Reference Synthesis Example 3]

[0311] A mixed solution of 200 parts by weight of tetrahydrofuran, 9 parts by weight of an unsaturated compound containing a fluorine unit represented by the above chemical formula 3A, and 91 parts by weight of (hydroxyethyl) methacrylate was added to a flask equipped with a cooling tube and a stirrer, and then 10 parts by weight of 2,2'-azobis(2,4-dimethylvaleronitrile) was added. After nitrogen substitution in the flask, the reaction solution was slowly stirred and heated to 55° C. for 20 hours to prepare an acrylic copolymer.

[0312] After adding 400 parts by weight of tetrahydrofuran, 100 parts by weight of the acrylic copolymer and 50 parts by weight of 2-isocyanatoethyl acrylate and mixing them thoroughly, 0.05 parts by weight of dibutyltin dilaurate was added, and then the temperature was raised to 40° C. and kept for 12 hours for reaction. After the reaction was completed, the polymer solution was purified and dried, and the weight average molecular weight of the final polymer was 15,000.

[0313] At this time, the weight average molecular weight is measured by the standard analysis method of gel permeation chromatography (GPC) used in the e2695 Alliance Separation Module of Water Company. The weight average molecular weight is the average molecular weight in terms of polystyrene measured by GPC. The column combination used is a pore size of Three types of Acquity APC XT (2.5μm, 4.6mm x 150mm).

[0314] [Reference Synthesis Example 4]

[0315] A mixed solution of 200 parts by weight of tetrahydrofuran, 61 parts by weight of an unsaturated compound containing a fluorine unit represented by the above chemical formula 4A, and 39 parts by weight of an unsaturated compound containing a hydroxyl group represented by the above chemical formula 2B was added to a flask with a cooling tube and a stirrer, and then 11 parts by weight of 2,2'-azobis(2,4-dimethylvaleronitrile) was added. After nitrogen substitution in the flask, the reaction solution was slowly stirred and heated to 55°C for 20 hours to prepare an acrylic copolymer.

[0316] After adding 400 parts by weight of tetrahydrofuran, 100 parts by weight of the acrylic copolymer and 20 parts by weight of 2-isocyanatoethyl acrylate and mixing them thoroughly, 0.05 parts by weight of dibutyltin dilaurate was added, and then the temperature was raised to 40° C. and kept for 12 hours for reaction. After the reaction was completed, the polymer solution was purified and dried, and the weight average molecular weight of the final polymer was 20,000.

[0317] At this time, the weight average molecular weight is measured by the standard analysis method of gel permeation chromatography (GPC) used in the e2695 Alliance Separation Module of Water Company. The weight average molecular weight is the average molecular weight in terms of polystyrene measured by GPC. The column combination used is a pore size of Three types of Acquity APC XT (2.5μm, 4.6mm x 150mm).

[0318] The compositions of the alkali-soluble resin and the fluorine-based resin compound of Chemical Formula 1 prepared by the above method are shown in Tables 1 and 2 below.

[0319] [Table 1]

[0320]

[0321] [Table 2]

[0322]

[0323]

[0324] [Chemical formula 1a]

[0325]

[0326] [Chemical formula 3]

[0327]

[0328] In the above Chemical Formula 3, R1=H, X3=CH2CH2, and m=1.

[0329] [Chemical formula 6]

[0330]

[0331] In the above chemical formula 6, R1=H, X 10 =CH2CH2, l=3.

[0332] [Chemical formula 7]

[0333]

[0334] In the above Chemical Formula 7, R1=H, X1=CH2CH2.

[0335] [Chemical formula 8]

[0336]

[0337] In the above Chemical Formula 8, R1=H, X8=CH2.

[0338] <Examples, Reference Examples, and Comparative Examples: Preparation of Photosensitive Resin Compositions and Optical Components>

[0339] Prepare the alkali-soluble resin, fluorine-based resin, photoinitiator, ethylenically unsaturated compound (multifunctional compound) and pigment shown in Tables 1 to 5. At this time, as shown in Table 5, for the components of the black pigment represented by each pigment number, a single black pigment or carbon black, or a mixture of one or more black, red, blue and violet pigments is used.

[0340] Then, according to the components in Tables 6 to 9, an alkali-soluble resin, a fluorine-based resin, a photoinitiator, an ethylenically unsaturated compound, a pigment and an organic solvent of polyethylene glycol methyl ether acetate (PGMEA) were uniformly mixed under stirring so that the solid content was about 20 weight %, thereby preparing the photosensitive resin compositions of the embodiments, reference examples and comparative examples.

[0341] The photosensitive resin composition was spin-coated on an ITO substrate, and then pre-baked in an oven at 120°C for 2 minutes, developed with a potassium hydroxide aqueous solution having an electrical conductivity of 1,950 μS / cm at 23°C for 100 seconds, and then washed with ultrapure water for 80 seconds. For final curing, it was heated in an oven at 230°C for 20 minutes to form a cured film. At this time, the thickness of the formed cured film was about 12 μm.

[0342] [Table 3]

[0343] No. Photoinitiator 1 1,2-Octanediol-1[(4-phenylthio)phenyl]-2-benzoyl-oxime 2 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]ethanone-1-O-acetyl oxime 3 (E)-2-(Acetoxyimino)-1-(9,9-diethyl-9H-fluoren-2-yl)butanone 4 Phenyl(4-methoxyphenyl)iodine arsenic hexafluoride

[0344] [Table 4]

[0345] No. Ethylenically unsaturated compounds 1 Dipentaerythritol hexaacrylate 2 Ditrimethylolpropane tetraacrylate 3 Trimethylolpropane triacrylate 4 1,6-Hexanediol diacrylate 5 Tricyclodecane dimethanol diacrylate 6 MIRAMER MU9500 (Miwon Specialty Chemicals Co., Ltd.) 7 MIRAMER MU9800 (Miwon Specialty Chemicals Co., Ltd.) 8 MIRAMER SC2100 (Miwon Specialty Chemicals Co., Ltd.) 9 MIRAMER PU640 (Miwon Specialty Chemicals Co., Ltd.) 10 Polygomer PN-4911 (Water Quality Analysis Instrument Co., Ltd.)

[0346] [Table 5]

[0347]

[0348]

[0349] <Test Example: Evaluation of Physical Properties of Cured Film Pattern of Photosensitive Resin Composition>

[0350] The physical properties of the cured films (optical films) formed in the above-mentioned Examples, Reference Examples and Comparative Examples were evaluated by the following methods. The results are shown in Table 10.

[0351] *Methods for measuring physical properties of optical films

[0352] 1) Sensitivity

[0353] The film formed as above was irradiated with a predetermined pattern mask at an intensity of 220 mW / cm at 365 to 435 nm at 1 second intervals. 2 UV light for 1 to 20 seconds. Then, develop with a potassium hydroxide aqueous solution with a conductivity of 1,950μS / cm at 23°C for 100 seconds, and then wash with ultrapure water for 80 seconds. For final curing, heat at 230°C in an oven for 20 minutes to obtain a patterned film. Using a thickness measuring device (P-16+, KLA-Tencor), based on the critical dimension (CD) of 20μm for line width and spacing (Line&Space), the exposure amount at which the residual film rate change begins to become less than 1% is measured as the sensitivity.

[0354] determination

[0355] ◎: The exposure dose is 100 mJ or less for the residual film rate change to be within 1%.

[0356] ○: The exposure dose at which the residual film rate change is within 1% is 100 to 150 mJ

[0357] X: The exposure dose for the residual film rate change to be within 1% is 150mJ or more

[0358] 2) Coating properties

[0359] The photosensitive resin composition was spin-coated or slit-coated on a glass substrate, pre-dried in a vacuum chamber, and then pre-baked at 120° C. for 100 seconds. The thickness distribution of the cured film was indicated by the symbols based on the following standard.

[0360] determination

[0361] ○: Thickness distribution within 5%

[0362] △: Thickness distribution is 5-10%

[0363] X: Thickness distribution greater than 10%

[0364] 3) Defoaming properties

[0365] After 150 ml of the photosensitive resin composition was placed in a 1,000 ml graduated cylinder, N2 gas equipped with a bubble filter was injected at a uniform flow rate, and the gas was shut off when the bubble generation volume reached 600 ml. After the bubble generation, the time for the bubble to completely disappear was measured.

[0366] determination

[0367] ○: Defoaming time is less than 60 seconds

[0368] △: Defoaming time is 60 to 90 seconds

[0369] X: Defoaming time is more than 90 seconds

[0370] 4) Liquid repellency (surface energy) of the exposed part

[0371] For the cured film prepared by the above method, the surface energy (unit: dyne / cm) of the exposed portion was measured according to the Owens-Wendt equation to evaluate the liquid repellency.

[0372] For the surface energy measurement, the contact angles of ultrapure water and diiodomethane were measured using a contact angle measuring device (DSA-100, KRUSS), and the surface energy was determined by the Owens-Wendt equation of the following mathematical formula 1.

[0373] [Mathematical formula 1]

[0374] (1+cosθ) / 2=[(γ s d ) 1 / 2 (γ l d ) 1 / 2 ] / γ l +[(γ s p ) 1 / 2 (γ l p ) 1 / 2 ] / γ l ]

[0375] In the above mathematical formula 1,

[0376] θ is the contact angle between a drop of ultrapure water and diiodomethane dropped on the sample surface and the surface.

[0377] γs d represents the dispersive force, γ s p represents polar interaction,

[0378] Surface energy (γ s ) can be determined as γ s d With γ s p sum.

[0379] γ l , γ l d and γ l p The following values ​​apply,

[0380] Ultrapure water: γ l =72.8dyne / cm,γ l d =21.8dyne / cmγ l p =51.0dyne / cm

[0381] Diiodomethane: γ l =50.8dyne / cm,γ l d =49.5dyne / cmγ l p =1.3dyne / cm.

[0382] determination

[0383] ◎: Surface energy is less than 25 dyne / cm

[0384] ○: Surface energy is 25 to 30 dyne / cm

[0385] △: Surface energy greater than 30 dyne / cm2 to less than 35 dyne / cm2

[0386] X: Surface energy is 35 dyne / cm or more

[0387] 5) Ink leveling properties (surface energy) of non-exposed areas

[0388] For the cured film prepared by the above method, the surface energy (unit: dyne / cm) of the non-exposed portion was measured according to the Owens-Wendt equation to evaluate the ink leveling property.

[0389] For the surface energy measurement, the contact angles of ultrapure water and diiodomethane were measured using a contact angle measuring device (DSA-100, KRUSS), and the surface energy was determined by the Owens-Wendt equation of the following mathematical formula 1.

[0390] [Mathematical formula 1]

[0391] (1+cosθ) / 2=[(γ s d ) 1 / 2 (γ l d ) 1 / 2 ] / γ l +[(γ s p ) 1 / 2 (γ l p ) 1 / 2 ] / γ l ]

[0392] In the above mathematical formula 1,

[0393] θ is the contact angle between a drop of ultrapure water and diiodomethane dropped on the sample surface and the surface.

[0394] γ s d represents the dispersive force, γ s p represents polar interaction,

[0395] Surface energy (γ s ) can be determined as γ s d With γ s p sum.

[0396] γ l , γ l d and γ l p Use the following values,

[0397] Ultrapure water: γ l =72.8dyne / cm,γ l d =21.8dyne / cmγ l p =51.0dyne / cm

[0398] Diiodomethane: γ l =50.8dyne / cm,γ ld =49.5dyne / cmγ l p =1.3dyne / cm.

[0399] determination

[0400] ◎: Surface energy greater than 40 dyne / cm

[0401] ○: Surface energy is 35-40 dyne / cm

[0402] △: Surface energy is 30-35 dyne / cm

[0403] X: Surface energy is 30 dyne / cm

[0404] 6) Reliability

[0405] The cured film was formed in the same manner as in the above sensitivity evaluation, but a pattern was formed on the ITO substrate. Figure 1 The same shape of the cured film pattern, and EL was evaporated. Al was evaporated on the top as the cathode electrode, and the encapsulation process was performed. The time (T97) for the brightness of the device to drop by 3% in the On state was evaluated based on 85°C and 85% RH.

[0406] determination

[0407] ○: T97 ensures more than 1,000 hours

[0408] △: T97 ensures 500 to 1,000 hours

[0409] X: T97 is less than 500 hours

[0410] 7) Optical density

[0411] The optical density (OD) of the partition wall defined by the following mathematical formula 2 was measured.

[0412] [Mathematical formula 2]

[0413] Optical density (OD) = 2-logT550

[0414] In the above Mathematical Formula 2, T550 represents the light transmittance (%) with respect to light of 550 nm measured at a thickness of 1 μm.

[0415] In other words, in the above-mentioned cured film preparation method, after preparing a cured film with a post-baking thickness of 1.0 μm without using a mask, the transmittance of the cured film at 550 nm is measured using an optical densitometer (361T, Xlite Company) to obtain the optical density for a thickness of 1.0 μm.

[0416] [Table 6]

[0417]

[0418]

[0419] [Table 7]

[0420]

[0421]

[0422] [Table 8]

[0423]

[0424]

[0425] [Table 9]

[0426]

[0427]

[0428] [Table 10]

[0429]

[0430]

[0431] [Table 11]

[0432]

[0433]

[0434] [Table 12]

[0435]

[0436] [Table 13]

[0437]

[0438]

[0439]

[0440] Note) In Table 13, for the Examples, Reference Examples, and Comparative Examples that do not show the optical density, all are 0 because they do not contain a black pigment.

[0441] From the results in Table 13 above, compared with Comparative Examples 1 to 3, Examples 1 to 7 have good coating properties, defoaming characteristics and ink leveling properties in the non-exposed area, and are excellent in sensitivity, liquid repellency and reliability in the exposed area.

[0442] In addition, compared with Comparative Examples 4 to 6, Examples 8 to 14 further comprising a black pigment also exhibited good coating properties, defoaming properties, ink leveling properties and optical density of the non-exposed portion, and exhibited excellent sensitivity, liquid repellency and reliability.

[0443] In contrast, when the photosensitive resin compositions of Comparative Examples 1 to 12 were used, one or more of the various properties of the cured films and their patterns were inferior to those of the Examples. In particular, for the Comparative Examples, due to the deteriorated liquid repellency, the reliability was reduced, and when applied to display elements, the residue of the photosensitive resin composition may remain outside the liquid repellent partition wall pattern portion, and it may also be difficult to form a flat coating film.

[0444] On the other hand, Reference Examples 1 to 23 showed sensitivity, coating properties, defoaming properties, leveling properties of non-exposed areas, liquid repellency of exposed areas, and reliability at or above the same level as the Comparative Examples. However, Reference Examples 1 to 14 did not use a long-chain flexible structure as the fluorine-based resin, and thus had relatively poor coating properties, defoaming properties, liquid repellency of exposed areas, and ink leveling properties of non-exposed areas.

[0445] <Test Example: Evaluation of Physical Properties of Display Elements According to Process Conditions>

[0446] The display element was prepared using the same components as in Example 1, but when the process conditions were changed as shown in the following table, the respective liquid repellency and ink leveling properties were evaluated (the evaluation method was the same as the results in Table 13 above).

[0447] [Table 14]

[0448]

[0449] As shown in Table 14, it can be seen that the liquid repellency and leveling properties may vary depending on the process conditions. Therefore, in order for the display element of the present invention to include partition walls with excellent liquid repellency and wettability, it is necessary to form the partition walls using appropriate materials and processes.

Claims

1. A display element, wherein: Include: Partition walls; and The color filter layer defined by the partition wall, The partition wall comprises: Alkali soluble resin derivatives; and Fluorine resin derivatives, The surface energy of the exposed part is less than 35 dyne / cm. The surface energy of the non-exposed portion is 35 dyne / cm or more.

2. The display element according to claim 1, wherein The fluorine atomic ratio in the cross section of the exposure portion of the partition wall is 0.001 to 1 mass %.

3. The display element according to claim 1, wherein: The surface energy of the non-exposed portion is greater than 40 dyne / cm.

4. The display element according to claim 1, wherein: The surface energy of the exposed portion is 25 dyne / cm or less.

5. The display element according to claim 1, wherein The surface energy difference between the non-exposed portion and the exposed portion is 15 dyne / cm or more.

6. The display element according to claim 1, wherein: The optical density of the partition wall defined by the following mathematical formula 2 is 0.1 to 3.0, [Mathematical formula 2] Optical density (OD) = 2-logT550 In the above Mathematical Formula 2, T550 represents the light transmittance (%) with respect to light of 550 nm measured at a thickness of 1 μm.

7. A photosensitive resin composition for forming a partition wall of a display element according to claim 1, wherein: The photosensitive resin composition comprises: a) alkali soluble resin; b) Fluorine resin; c) ethylenically unsaturated compounds; and d) Photoinitiator.

8. The photosensitive resin composition according to claim 7, wherein The fluorine-based resin comprises repeating units represented by the following chemical formulas 1 and 1-1: [Chemical formula 1] [Chemical formula 1-1] In the above chemical formulas 1 and 1-1, a and b represent the molar ratio between the repeating units, a+b=100, a (fluorine monomer) is 10 to 60, and the molar ratio between the repeating units is based on 2D-NMR (H-NMR, F-NMR) analysis, x and y are integers from 1 to 8, R1 and R2 are each independently hydrogen or methyl, R3 is a fluoroalkyl group having 1 to 20 carbon atoms which may have an ethereal oxygen atom, and a part of the fluorine in at least one of the fluoroalkyl groups may be substituted with hydrogen. R4 is a branched group having 0 to 50 carbon atoms and having any one or more structures selected from the group consisting of a carbamate group, a urea group, an amino group, a hydroxyl group, an acryloyl group, an ether group, and an ester group.

9. The photosensitive resin composition according to claim 8, wherein R3 in the above chemical formula 1 is selected from -(CF2)oCF3, -(CF2)pCF2H and -CF2(OCF2CF2)qCF3 (wherein, o and p are each independently an integer from 1 to 7, and q is an integer from 1 to 3).

10. The photosensitive resin composition according to claim 8, wherein R4 in the above chemical formula 1-1 is a structure of the following chemical formula 1-2: [Chemical formula 1-2] In the above chemical formula 1-2, m is an integer from 0 to 5, Z1 and Z3 each independently represent an organic group having 1 to 20 carbon atoms, Z2 is an organic group containing any one or more structures of a carbamate group, a urea group, a hydroxyl group, an ether group, and an ester group, R1 is hydrogen or methyl.

11. The photosensitive resin composition according to claim 8, wherein The R4 is a substituent selected from the group represented by the following Chemical Formula 2 to Chemical Formula 6: [Chemical formula 2] In the above chemical formula 2, R1 is hydrogen or methyl, X2 represents an organic group having 1 to 20 carbon atoms, [Chemical formula 3] In the above chemical formula 3, R1 is hydrogen or methyl, X3 represents an organic group having 1 to 20 carbon atoms, and m is an integer from 1 to 5. [Chemical formula 4] In the above chemical formula 4, R1 is hydrogen or methyl, X4 represents an organic group having 1 to 20 carbon atoms, and m is an integer from 1 to 5. [Chemical formula 5] In the above chemical formula 5, R1 is hydrogen or methyl, X6 represents an organic group having 1 to 20 carbon atoms, and m is an integer from 1 to 5. [Chemical formula 6] In the above chemical formula 6, R1 is hydrogen or methyl, X 10 represents an organic group having 1 to 20 carbon atoms, and l is an integer of 1 to 13.

12. The photosensitive resin composition according to claim 7, wherein b) the fluorine-based resin is present in an amount of 0.01 to 10 parts by weight relative to 100 parts by weight of the total solid content representing the total content of a) the alkali-soluble resin, c) the ethylenically unsaturated compound and d) the photoinitiator.

13. The photosensitive resin composition according to claim 7, wherein The ethylenically unsaturated compound includes a multifunctional acrylic monomer or a urethane acrylate monomer.

14. The photosensitive resin composition according to claim 13, wherein The multifunctional acrylic monomer includes one or more selected from the group consisting of 1,4-butanediol diacrylate, 1,3-butanediol diacrylate, ethylene glycol diacrylate, trimethylol propane diacrylate, trimethylol propane triacrylate, pentaerythritol triacrylate, pentaerythritol tetraacrylate, triethylene glycol diacrylate, polyethylene glycol diacrylate, dipentaerythritol hexaacrylate, dipentaerythritol triacrylate, dipentaerythritol diacrylate, sorbitol triacrylate, bisphenol A diacrylate derivatives, dipentaerythritol polyacrylate and their methacrylates.

15. The photosensitive resin composition according to claim 13, wherein The urethane acrylate oligomer includes at least one selected from the group consisting of aliphatic urethane (meth)acrylate oligomers having 2 to 20 unsaturated functional groups, aromatic urethane (meth)acrylate oligomers, epoxy (meth)acrylate oligomers, polyester (meth)acrylate oligomers, silicone (meth)acrylate oligomers, melamine (meth)acrylate oligomers, and dendritic (meth)acrylate oligomers.

16. The photosensitive resin composition according to claim 7, wherein The photoinitiator includes at least one selected from the group consisting of carbazole initiators, oxime ester initiators, aminoalkylphenone initiators, and acylphosphine oxide initiators.

17. The photosensitive resin composition according to claim 7, wherein With respect to 100 parts by weight of a) alkali-soluble resin, The photosensitive resin composition comprises: c) 10 to 200 parts by weight of an ethylenically unsaturated compound; and d) 1 to 20 parts by weight of photoinitiator.

18. The photosensitive resin composition according to claim 7, wherein The photosensitive resin composition further includes at least one selected from the group consisting of e) a black pigment or a pigment mixture containing a pigment that is black in a mixed state, and f) a silane coupling agent.

19. The photosensitive resin composition according to claim 18, wherein The black pigment includes at least one selected from the group consisting of aniline black, perylene black, titanium black, cyanine black, lignin black, lactam black, carbon black, RGB black, RBY black, and RBV black.

20. The photosensitive resin composition according to claim 19, wherein The pigment mixture includes two or more selected from red pigment, blue pigment, yellow pigment, green pigment and violet pigment, and exhibits black color in a mixed state.